2018
DOI: 10.1016/j.ejogrb.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of miscarriage in women with viable intrauterine pregnancy—A systematic review and diagnostic accuracy meta-analysis

Abstract: Both ultrasound and biochemical markers either alone or in combination have been described in the literature for the prediction of miscarriage. We performed this systematic review and meta-analysis to determine the best combination of biochemical, ultrasound and demographic markers to predict miscarriage in women with viable intrauterine pregnancy. The electronic database search included Medline (1946-June 2017), Embase (1980-June 2017), CINAHL (1981-June 2017) and Cochrane library. Key MESH and Boolean terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…When present, the size, location and content of the IUH did not impact on the risk of miscarriage. This finding is similar to that of a recent meta-analysis aiming to assess predictors of miscarriage in viable pregnancy, which also found that IUH was not associated with miscarriage 39 .…”
Section: Discussionsupporting
confidence: 90%
“…When present, the size, location and content of the IUH did not impact on the risk of miscarriage. This finding is similar to that of a recent meta-analysis aiming to assess predictors of miscarriage in viable pregnancy, which also found that IUH was not associated with miscarriage 39 .…”
Section: Discussionsupporting
confidence: 90%
“…Despite the study limitations, we believe the high specificity of bradycardia for prediction of miscarriage is a useful marker for emergency physicians to more accurately counsel patients, manage expectations, and ensure referral for repeated ultrasonography within 7 to 10 days. 4…”
Section: Commentarymentioning
confidence: 99%
“…15 In a recent study of 61 miscarriages, abnormal size of gestational sac and yolk sac appeared as early as 6 weeks of gestation, followed by abnormal changes in fetal heart rate and CRL at 7 and 8 weeks. 14 Although subchorionic haematoma was found to be a predictor of miscarriage in a metaanalysis 11 and in the study by Wan et al, 7 a recent study on pregnancies with detectable fetal heartbeat did not concur with these findings. 10 A meta-analysis of 15 studies including 1263 women with threatened miscarriage found that serum CA 125 is the only serum marker that is useful in predicting outcome of a pregnancy with a viable fetus, whereas serum human chorionic gonadotropin and progesterone are not useful.…”
mentioning
confidence: 96%
“…7,9,10 A meta-analysis of 18 eligible studies on ultrasound markers among 5584 women found that fetal bradycardia is the most significant marker, with a sensitivity of 84.2% in the prediction of miscarriage. 11 A more recent study found that the combination of low fetal heart rate and small CRL increases the risk of subsequent pregnancy loss, from 5.0% to 21%. 10 Because fetal heart rate varies with gestation, cut-offs for low fetal heart rate of ≤122, ≤123, and ≤158 beats per minute for gestational weeks 6, 7, and 8, respectively, have been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation